2017
DOI: 10.1038/srep39712
|View full text |Cite
|
Sign up to set email alerts
|

Osseous differentiation of human fat tissue grafts: From tissue engineering to tissue differentiation

Abstract: Conventional bone tissue engineering approaches require isolation and in vitro propagation of autologous cells, followed by seeding on a variety of scaffolds. Those protracted procedures impede the clinical applications. Here we report the transdifferentiation of human fat tissue fragments retrieved from subcutaneous fat into tissue with bone characteristics in vitro without prior cell isolation and propagation. 3D collagen-I cultures of human fat tissue were cultivated either in growth medium or in osteogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 66 publications
(77 reference statements)
0
9
0
Order By: Relevance
“…The question whether the osteogenic differentiation capacity or the potential to deliver high levels of transgene is more important for effective bone regeneration can only be answered by future in vivo experiments. Interestingly, recent in vitro studies could prove that human fat tissue (Bondarava et al, ) and human muscle tissue (Miao et al, ) can transdifferentiate into mineralized tissue with bone‐like characteristics. These results suggest that the grafted gene‐activated tissue fragments used in the experiments of Betz and colleagues (Betz et al, ; Betz et al, ) contributed to the formation of new bone in vivo through transdifferentiation and not only through the local effects of the delivered BMP on the environment of the lesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The question whether the osteogenic differentiation capacity or the potential to deliver high levels of transgene is more important for effective bone regeneration can only be answered by future in vivo experiments. Interestingly, recent in vitro studies could prove that human fat tissue (Bondarava et al, ) and human muscle tissue (Miao et al, ) can transdifferentiate into mineralized tissue with bone‐like characteristics. These results suggest that the grafted gene‐activated tissue fragments used in the experiments of Betz and colleagues (Betz et al, ; Betz et al, ) contributed to the formation of new bone in vivo through transdifferentiation and not only through the local effects of the delivered BMP on the environment of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…The implantation of BMP‐2 gene‐activated fat led to fast and robust structural and functional healing of femoral defects. Moreover, in recent work, it could be demonstrated that human fat tissue can transdifferentiate into bone‐like tissue (Bondarava et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For hADSCs, cells were donated to our lab by Maryna et al . 69 , whereas chondrocytes and hBMSCs were obtained from Lonza (Lonza, Basel, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…The authors attributed the compromised results to large defect sizes, rapid resorption of the ceramic scaffolds, and possibly the lack of osteoinductive signals in the form of rhBMP‐2. In context, a recent study demonstrated enhanced osteogenic differentiation of cells from “whole adipose tissue” stimulated by rhBMP‐2 compared to stimulation by osteogenic medium alone (Bondarava et al., ).…”
Section: Discussionmentioning
confidence: 99%